Company Characteristics Influence Tax Avoidance - Utami, Nabila Putri; Siahaan, Magda (Media Bisnis, 2024)
The objective of this study is to obtain empirical evidence regarding the effect of firm size, firm age, the presence of an independent board of commissioners, the existence of an audit committee, sales growth, leverage, and asset returns on the phenomenon of tax avoidance. This study employs a sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. A purposive sampling method was employed to select a sample of 61 companies that met the requisite criteria. The study employed multiple analytical methods, and the results indicated that the leverage variable affected tax avoidance. Conversely, the variables of firm size, firm age, independent board of commissioners, audit committee, sales growth, and return on assets were found not to affect tax avoidance.